THE SCOPE AND OBJECT OF FORENSIC LAND SURVEY - A. Shalamygina (Теория и практика судебной экспертизы)
The paper examines such concepts of forensic theory as «scope» and «object» of forensic inquiry, as applied to forensic land surveys, and o"ers their general de#nitions. The author analyzes di"erent researchers' perspectives on determining the scope of forensic examination, and o"ers her own de#nition of the scope of forensic examination as applied to forensic land survey. To clarify the de#nition even further, several types of land disputes are discussed to provide the rationale for the author's conclusion as to what constitutes the scope of forensic land survey. A de#nition of the object of forensic land survey is also proposed, and illustrated with some examples. The author observes and explains apparent inconsistencies between the current designation of this #eld of forensic inquiry and its objects, and explains the sources of these inconsistencies.